Porcine-Stimulated Human Tr1 Cells Showed Enhanced Suppression in Xenoantigen Stimulation Response - Xiaoting Chen (Hindawi Limited, 2021)
Type 1 regulatory T (Tr1) cells play a fundamental role in maintaining and inducing immune tolerance. Our preliminary study demonstrated that an interleukin- (IL-) 10-mediated pathway is a possible regulatory mechanism underlying the xenoantigen-specific human Treg enhanced suppressive capacity. Here, we developed a feasible protocol for expanding IL-10-induced xenoantigen-specific human Tr1 cells in vitro which would be more efficient in transplantation immunotherapy efficiency. In this study, xenoantigen-specific Tr1 cells are generated from human naive CD4+ T cells expanded for two subsequent xenoantigen-stimulation cycles with recombinant human IL-10. The phenotype and suppressive capacity of xenoantigen-stimulated Tr1 cells are assessed, and the mechanism of their suppression is studied. Tr1 cells can be induced by porcine xenoantigen stimulation combined with IL-10, IL-2, and IL-15, displaying an increased expression of CD49b, CTLA-4, and LAG-3 without expressing Foxp3 which also showed an effector memory Treg phenotype and expressed high levels of CD39. After xenoantigen stimulation, the IL-10 and IL-5 gene expression in Tr1 cells increased, secreting more IL-10, and xenoantigen-stimulated Tr1 cells changed their T cell receptor (TCR) Vβ repertoire, increasing the expression of TCR Vβ2, TCR Vβ9, and TCR Vβ13. In a pig to human mixed lymphocyte reaction (MLR), xenoantigen-stimulated Tr1 cells displayed enhanced suppressive capacity via CD39 in a dose-dependent manner. Moreover, IL-5 could affect the proliferation of xenoantigen-specific Tr1 cells, but not their phenotypes’ expression. This study provides a theory and feasible method for immune tolerance induction in clinical xenotransplantation.